RETRACTED: Biomedical microelectromechanical systems (BioMEMS): Revolution in drug delivery and analytical techniques - Rishad R. Jivani; Gaurang J. Lakhtaria; Dhaval D. Patadiya; Laxman D. Patel; Nurrudin P. Jivani; Bhagyesh P. Jhala (Elsevier, 2016)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal).This article has been retracted at the request of This article has been retracted at the request of the Editor-in-Chief.The authors have plagiarized part of a paper that had already appeared in Advanced Drug Delivery Reviews 64 (2012) 496-507 doi:10.1016/j.addr.2011.11.013. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.